Sosialisasi Literasi Ekonomi Syariah Bagi Generasi Milenial pada Organisasi Pemuda Di Desa Bunder Jatiluhur Purwakarta - Rohmat, Siti (STIE Syariah Indonesia Purwakarta, 2022)
The lack of public interest in Islamic banking is a result of the lack of Islamic Economic Literacy. The public is more aware of conventional banking which contains elements of usury. Therefore, it is necessary to socialize sharia economic literacy so that people can avoid non-sharia practices that will be very detrimental to society. The purpose of this service is to socialize Islamic Economic Literacy to the Millennial Generation or youth organizations in Bunder Village Jatiluhur, Purwakarta. This service method is carried out by socializing about Islamic Economic Literacy which consists of lectures, discussions, and image visualization. The results of community service activities regarding the Socialization of Sharia Economic Literacy for Millennial Generation at Youth Organizations in Bunder Village Jatiluhur Purwakarta went smoothly and well as planned. With this Sharia Economic Literacy Socialization, Youth Organizations and Bunder Jatiluhur Purwakarta village communities can understand the concept of Sharia economics, can slowly apply Sharia economic concepts in everyday life, especially for the millennial generation, and can avoid the trap of usury or